Ujaran Kebencian Terhadap Selebgram Azizah Salsha Melalui Kajian Linguistik Forensik - Patihah, Marwah Ernia; Wiwik Surya Utami, Wiwik Surya Utami (Ruang Kata, 2025)
This study aims to explore the forms of hate speech directed at Instagram influencer Azizah Salsha on social media, particularly Instagram, using a forensic linguistic approach. The main focus of this research is to identify the types of hate speech and the linguistic elements used in negative comments aimed at public figure. The method employed is descriptive qualitative, with data collected through documentation of comments from Azizah Salsha's Instagram posts. The findings reveal that the hate speech received by Azizah Salsha can be classified into several categories: insults, incitement, dissemination of false information, and provocation. These results indicate that hate speech not only contains degrading linguistic elements but also has serious social and psychological impacts. This research contributes to the field of forensic linguistics and provides a critical understanding of the importance of language ethics in digital spaces.